Healthcare-associated infections in long-term care facilities: a systematic review and meta-analysis of point prevalence studies - Karin Thursky; David Dunt; Leon J Worth; Rodney James; Stephanie K Tanamas; Janet K Sluggett; Noleen Bennett; Courtney Ierano; Michael J Malloy; Eliza Watson (BMJ Public Health)
Objectives Residents of long-term care facilities (LTCFs) are especially vulnerable to acquiring healthcare-associated infections (HAIs). Our systematic review and meta-analysis estimated the burden of HAIs, identified the most frequent HAIs and explored the impact of facility-level and surveillance methodological differences on HAI burden in LTCFs, as determined by point prevalence studies (PPS).Design Systematic review and meta-analysis.Data sources Bibliographic databases MEDLINE (Ovid), Embase (Ovid) and CINAHL (EBSCOhost) were searched for potentially eligible English-language original research publications. References of short-listed full-text publications, the European Centre for Disease Control and Prevention website and an unpublished 2016–2022 Australian Aged Care PPS report were also checked.Eligibility criteria PPS monitoring HAIs, published and undertaken between January 1991 and June 2023 in LTCFs.Data extraction and synthesis Two reviewers independently screened for eligible PPS and if included, assessed risk of bias for each PPS using the Joanna Briggs Institute (JBI) critical appraisal tool for prevalence studies. Meta-analysis was performed using a generalised linear mixed model.Results 31 publications (including 123 PPS from 33 countries encompassing 709 860 residents) were included. Nine PPS (7.3%) were allocated a JBI quality score greater than 80% while 30 PPS (24.4%) were allocated a score between 70% and 80%. The overall pooled HAI point prevalence was 3.5% (95% CI 3.1% to 4.0%); 3.9% (95% CI 3.2% to 4.7%) when higher bias-risk PPS (<70% quality score) were excluded. Of 120 PPS, the most frequently reported HAIs were urinary tract (UTIs; 38.9%), respiratory tract (RTIs; 33.6%) and skin or soft tissue (SSTIs; 23.7%) infections. HAI point prevalence varied by geographical region (p<0.001), study decade (p<0.001) and HAI surveillance definitions used (p<0.001). There was no difference across facility types (p=0.57) or season (p=0.46).Conclusions HAIs remain a global public health problem and threat to the safety of LTCF residents; effective infection prevention and control strategies to reduce HAIs in LTCFs are still required. Guidance specifically about the prevention and management of UTIs, RTIs and SSTIs should be prioritised.PROSPERO registration number CRD42023406844.